A coupled smeared crack-plasticity model in incremental sequentially linear analysis for mixed failure modes. (September 2022) - Yu, Chenjie
Highlights: The solver is robust for quasi-brittle materials. The material model is capable in simulating mixed failure modes. The material model resolves the limitations of a purely rotating crack model. Crack propagations are localized in in-plane failures of masonry walls. Abstract: In this paper, a coupled smeared crack-plasticity model is proposed in incremental sequentially linear analysis (ISLA) to simulate mixed failure modes of tension, shear and compression. ISLA provides a robust and extensible solution for quasi-brittle materials. The solution search path follows damage cycles sequentially with secant stiffness corresponding to local damage increments, which traces both damage history (explicit) and displacement history (implicit). The proposed rotating smeared crack model resolves the limitations of a purely rotating crack model in the case that the smallest and the largest principal stress value are almost the same or the situation that the principal directions interchange between the beginning and the end of a load step. ISLA with the proposed constitutive model were demonstrated by mixed flure modes of the in-plane tests with large overburdens of a double clamped short wall and a cantilever long wall. Stable post-peak results were computed for large displacements, and localized crack propagation was computed robustly and correctly.